2018
DOI: 10.1177/1940161218821098
|View full text |Cite
|
Sign up to set email alerts
|

The Populist Radical Right and the Media in the Benelux: Friend or Foe?

Abstract: Although most scholars acknowledge that the media play an instrumental role in furthering or limiting the spread of populism, the exact nature of the relationship between right-wing populist parties (RWPPs) and the media remains poorly understood. This article analyzes the various ways in which the media choose to deal with RWPPs in the Benelux region (i.e., Belgium, the Netherlands, and Luxembourg). Using evidence from interviews with media practitioners ( n = 46), the findings suggest that in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Even media outlets such as Fox News Channel deny Trump's anti-democratic bluster a stage, thereby showcasing that such an approach to far-right actors is perfectly viable (cf. de Jonge 2019). As in the US, the coronavirus pandemic has in most countries mainly resulted in support for actors that (also rhetorically) mostly aim for maintaining the status quo.…”
Section: Postscriptmentioning
confidence: 99%
“…Even media outlets such as Fox News Channel deny Trump's anti-democratic bluster a stage, thereby showcasing that such an approach to far-right actors is perfectly viable (cf. de Jonge 2019). As in the US, the coronavirus pandemic has in most countries mainly resulted in support for actors that (also rhetorically) mostly aim for maintaining the status quo.…”
Section: Postscriptmentioning
confidence: 99%
“…The ways in which the media approach the far right is shaped by journalistic norms (Ellinas 2010: 211) 10 . Flemish media practitioners have gradually become more accommodative towards PRRPs than their francophone colleagues, who adhere to strict demarcation (de Jonge 2019).…”
Section: Beyond Demand and Supply: Contextual Factorsmentioning
confidence: 99%
“…One type of response has come from within existing media institutions where media workers are rethinking the ways they cover events and controversies staged by populists. De Jonge () conducted research interviews with journalists in Belgium, the Netherlands, and Luxemburg and found that they had come to different strategies for how to cover far‐right populists in these regions. Phillips (), a media scholar, has developed a guide for journalists for better practices to help reduce journalists' role in “amplifying” the publicity of media manipulation practices associated with far‐right populists.…”
Section: Populism and The Politics Of Mediamentioning
confidence: 99%